Florida Solid and Hazardous Waste Regulation Handbook: Biological and Animal Waste Disposal - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Biological waste is defined in the Resource Recovery and Management Act as including, but not limited to, biomedical waste, diseased or dead animals, and other waste capable of transmitting pathogens to humans or animals. Other biological wastes are subject to lower standards of disposal than most other solid wastes. Because of the prevalence of agriculture in Florida, special rules apply to dead animals and poultry wastes. This is EDIS document FE460, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.